Penyuluhan Ibu Hamil dengan Tablet Fe, Nutrisi Ibu Hamil dan Tanda Bahaya Ibu Hamil di Wilayah Kelurahan Jenggot Kota Pekalongan - Miftachul Jannah; Swasti Artanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Community service program with the topic "Counseling Pregnant Women with Fe Tablets, Nutrition for Pregnant Women and Dangerous Signs of Pregnant Women in Jenggot, Pekalongan City" is aimed at Trimester II and III pregnant women to provide about pregnant women's knowledge about the benefits of Fe tablets , nutritional needs during pregnancy and pregnancy danger signs in the area of Jenggot, Pekalongan city. It is important to educate pregnant women about the benefits of Fe tablets during pregnancy because hemoglobin is needed for the body of pregnant women. During pregnancy, a pregnant woman needs to have high nutritious food and is sufficient for herself and her fetus. If a pregnant woman lacks nutrition and iron during pregnancy, it will cause problems, both for the mother and the fetus. Family and environmental factors will greatly affect pregnant women. Hopefully, pregnant women will have no abstinence to eat. This activity can be sustainable and encourage pregnant women to care during pregnancy whether to take Fe tablets, eat nutritious foods and understand the danger signs during pregnancy. In addition, a Pre Test and Post Test were conducted to determine the level of knowledge before and after counseling. The results obtained are that there is a significant increase in pregnant women in Jenggot, Pekalongan after counseling about Fe tablets, nutrition of pregnant women and pregnancy danger signs.